History of Changes in the Evaluation System on Membership Sports Organizations of the Korean Sport & Olympic Committee - Misuk Kim; Jayoung Kim; Jooyoung Kim (Korea Institute of Sport Science, 2021)
PURPOSE This study compared and analyzed the current status, system, and trend of evaluation and operation of member sports organizations of the Korean Sport & Olympic Committee from 2006 to 2020. METHODS A literature study was conducted for this study. RESULTS The 15-year evaluation was developed through three periods: preparation, execution, and construction. The preparation stage (2006-2009) was when the evaluation index development and operation system were established. The execution stage (2010-2016) is a critical time; when the current system was established. This was when evaluation perception was spread in the sports world and continuous changes such as evaluation system and operation, indicators. Finally, the construction stage (2017-2020) was when the evaluation system was established after integrating the Korean Sport & Olympic Committee and the National Sports Council. CONCLUSIONS It played a role in promoting balanced growth from organizational management to ethical management of sports organizations through preparation, execution, and construction. Further, the evaluation reflected the continuous development and change of the Korean sports community and one organizational assessment.